A PSPICE Circuit Modeling of Strained AlGaInN Laser Diode Based on the Multilevel Rate Equations - Lim, Dong Wook; Cho, Hyung Uk; Sung, Hyuk Kee; Yi, Jong Chang; Jhon, Young Min (OPTICAL SOC KOREA, 2009)
PSPICE circuit parameters of the blue laser diodes grown on wurtzite AlGaInN multiple quantum well structures were extracted directly from the three level rate equations. The relevant optical gain parameters were separately calculated from the self-consistent multiband Hamiltonian. The resulting equivalent circuit model for a blue laser diode was schematically presented, and its modulation characteristics, including the pulse response and the frequency response, have been demonstrated by rising a conventional PSPICE.
Keywords: QUANTUM-WELL LASERS